2022
DOI: 10.1038/s41419-022-05201-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy potentiates the cytotoxicity of the irreversible FGFR1-4 inhibitor FIIN-2 on lung adenocarcinoma

Abstract: For patients with platinum-resistant lung adenocarcinoma (LUAD), the exploration of new effective drug candidates is urgently needed. Fibroblast growth factor receptors (FGFRs) have been identified as promising targets for LUAD therapy. The purpose of this study was to determine the exact role of the irreversible FGFR1-4 inhibitor FIIN-2 in LUAD and to clarify its underlying molecular mechanisms. Our results demonstrated that FIIN-2 significantly inhibited the proliferation, colony formation, and migration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Recent work demonstrated that the FGFR1 signaling pathway has the effect to inhibit autophagy. [340] It might be a novel treatment plan that targets both the FGFR1 pathway and autophagy osimertinib-resistant NSCLC. Zhang et al found that both autophagy and the FGFR1 signaling pathway were activated in osimertinib-resistant NSCLC.…”
Section: Overcoming Resistance To Molecular Targeted Therapymentioning
confidence: 99%
“…Recent work demonstrated that the FGFR1 signaling pathway has the effect to inhibit autophagy. [340] It might be a novel treatment plan that targets both the FGFR1 pathway and autophagy osimertinib-resistant NSCLC. Zhang et al found that both autophagy and the FGFR1 signaling pathway were activated in osimertinib-resistant NSCLC.…”
Section: Overcoming Resistance To Molecular Targeted Therapymentioning
confidence: 99%